DNA Barcoding of Andaliman (Zanthoxylum acanthopodium DC) from North Sumatra Province of Indonesia Using Maturase K Gene - Suriani, Cicik (Trop Life Sci Res, 2021)
Andaliman (Zanthoxylum acanthopodium DC) is a native plant of North Sumatra province. Zanthoxylum acanthopodium is a member of Rutaceae family widely found in northern Sumatra, Indonesia. The aim of this study was to barcode Z. acanthopodium in North Sumatra province, Indonesia based on cpDNA maturase K (matK). Samples were collected in seven localities across six regions of North Sumatra province. Phylogenetic analysis was conducted using Maximum Likelihood method. The results of phylogenetic analysis indicate that Z. acanthopodium is a monophyletic group that is derived from a common ancestor. The results of the phylogenetic tree construction show that there is a grouping of accession between Z. acanthopodium species separate from other species in the Zanthoxylum genus as well as those of the Rutaceae family. The results showed that cpDNA matK marker can effectively be used as DNA barcoding to identify Z. acanthopodium.